Pelaksanaan Mediasi Hakim Mediator Di Pengadilan Agama Kota Padangsidempuan - Ramadhan, Nispu; Sirait, Adi Syahputra (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study examines the implementation of mediator judge mediation at the Padangsidempuan City Religious Court. This type of research is field research with a qualitative approach, the primary data source comes from Mediator Judges at the Padangsidempuan City Religious Court, while the secondary data from researchers are official documents, legal books, both journals and articles related to this research. Data collection techniques in this study used observation, interviews and documentation. Data analysis techniques in this study used descriptive qualitative analysis techniques. The results of this study are the level of effectiveness of the efforts of mediator judges in reconciling divorce cases at the Padangsidempuan City Religious Court, which can be categorized as not maximally effective by looking at the number of divorces that have occurred at the Padangsidempuan City Religious Court. While the factors that influence it are internal factors: legal factors, namely because of the regulations governing mediation with a limited time, actors or law enforcement factors, namely the success of the mediator judge in carrying out his duties in terms of mentality and personality. The facility or facility factor is that the Padangsidempuan City Religious Court has a special mediation room provided, but the parties and the mediator judge have not been able to make optimal use of it. And external factors: customary factors and community factors, namely the litigant party submits his case to the court only to determine whether the divorce is valid or not.